Comparison Analysis of Equivalent Static Earthquake and Spectrum Response Dynamics on Steel Structure - Diana Ningrum; Albertus Nahak; Nawir Rasidi (CV. Creative Tugu Pena, 2022)
The purpose of this study is to compare two methods of seismic load analysis, namely the static equivalent method and the dynamic response spectrum method. The case study is the integrated service building of Tribhuwana Tunggadewi University, Malang City which has 5 levels and is located in the 4 (medium) earthquake zone with moderate soil conditions. The research method used is descriptive quantitative. Collecting data of project drawings, as well as observations and interviews. Analysis method Equivalent static and dynamic response spectrum using software Staad Pro. The results compared are the base shear force (V), the floor lateral force (F), and the displacement or displacement. The result in the form of maximum internal force is analyzed to determine the capacity or ability of the profile to withstand combined loads. The comparison of base shear and displacement does not differ much from the two seismic analysis methods used. This insignificant difference is in accordance with the SNI that for structures with a height below 40m can be analyzed using equivalent statics, while in the case study it only has a height of 30m. So that the equivalent static analysis becomes more accurate to use because the analysis process is simpler than dynamic analysis, but for structures with a height above 5 floors it is recommended to use dynamic analysis. The results of the analysis of the ability of the steel profile on the cross section of the column and beam indicate a safe condition in carrying combined loads. Keywords: Volume Fraction, Cannabis Sativa Fibers, Fiber Composites